2019
DOI: 10.3390/jcm8122227
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Gut Microbiota in Lipid and Lipoprotein Metabolism

Abstract: Both environmental and genetic factors contribute to relative species abundance and metabolic characteristics of the intestinal microbiota. The intestinal microbiota and accompanying microbial metabolites differ substantially in those who are obese or have other metabolic disorders. Accumulating evidence from germ-free mice and antibiotic-treated animal models suggests that altered intestinal gut microbiota contributes significantly to metabolic disorders involving impaired glucose and lipid metabolism. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 166 publications
(203 reference statements)
1
75
0
3
Order By: Relevance
“…Recent studies have revealed that alteration of gut microbiota not only could affect the bile acid pool but also could influence the bile acid receptor signaling (i.e., FXR and TGR5). The FXR has been reported to be involved in glucose homeostasis, energy expenditure, and lipid metabolism ( 26 ). These observations provide insight into the potential function and mechanism of our identified microbial features, represented by the MRS, in host metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that alteration of gut microbiota not only could affect the bile acid pool but also could influence the bile acid receptor signaling (i.e., FXR and TGR5). The FXR has been reported to be involved in glucose homeostasis, energy expenditure, and lipid metabolism ( 26 ). These observations provide insight into the potential function and mechanism of our identified microbial features, represented by the MRS, in host metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have revealed that alteration of gut microbiota could 218 not only affect the bile acid pool, but also influence the bile acid receptor signaling 219 (i.e., FXR and TGR5). The FXR has been reported to be involved in glucose 220 homeostasis, energy expenditure, and lipid metabolism (20).These observations 221 provide insight into the potential function and mechanism of our identified microbial Mice transplanted with the gut microbiota from high MRS individuals, either at non-230 T2D or T2D status, showed significant increase in fasting glucose levels compared 231 with those from the low MRS individuals or germ-free control mice ( Fig.3E to F).…”
mentioning
confidence: 73%
“…This is in accordance with a recent proteomic investigation by Simon et al ( 31 ) where 24-h-long fasting was shown to cause an upregulation of Apo A-I in the jejunum of broiler chicken. Additionally, there are data indicating that both intestinal microbiota as well as gut microbiome-derived short-chain fatty acids (SCFAs) are also a potent stimulus of intestinal and liver lipoprotein formation ( 32 , 33 ). Taken together, the dynamic changes of APOA1 gene expression demonstrated in our study could be attributed to a concomitant combination of the aforementioned mechanism.…”
Section: Discussionmentioning
confidence: 99%